2020
DOI: 10.3389/fonc.2020.567616
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Combined Radiotherapy, Systemic Therapy, and Androgen Deprivation Therapy for Metastatic Hormone-Sensitive Prostate Cancer: A Network Meta-Analysis and Systematic Review

Abstract: Background: Recent randomized clinical trials have examined the efficacy of different combinations of systemic and local treatment approaches for metastatic hormone-sensitive prostate cancer (mHSPC). We compared the efficacy of these combined regimens in order to identify the optimal therapy for specific patient subgroups.Methods: The treatments were abiraterone (ABI), apalutamide (APA), docetaxel (DOC), enzalutamide (ENZ), and radiotherapy (RT) combined with androgen-deprivation therapy (ADT). Five electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…Of these 5 SRs, 3 were published in 2020, 13,16,17 1 in 2019, 14 and 1 in 2018. 15 The literature searches ranged from database inception to May 15, 2020.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these 5 SRs, 3 were published in 2020, 13,16,17 1 in 2019, 14 and 1 in 2018. 15 The literature searches ranged from database inception to May 15, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The primary author for 3 of the SRs were from China. 13,15,17 One SR was authored by an investigator in the US 16 and 1 from France. 14 Two primary studies were authored by investigators in Japan 18,19 and 1 by an investigator in Canada.…”
Section: Country Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…The same results were also obtained in another meta-analysis. 28 This meta-analysis included seven RCTs (ENZAMET, TITAN, GETUG-AFU-15, CHAARTED, STAMPEDE, LATITUDE, HORRAD) with 8820 patients. In the low-volume subgroup, ENZ, APA, docetaxel, AAP, and external beam radiation therapy (EBRT) to the prostate had superior OS than ADT alone; however, statistical significance was only observed for ENZ (HR, 0.38; 95% CI, 0.21–0.69) and EBRT (HR, 0.68; 95% CI, 0.54–0.87).…”
Section: The Rationale For a Paradigm Shift From The “All-comers” Toward The “Personalized” Approachmentioning
confidence: 99%
“…Meta-analysis of 2 RCTs that involved 2493 patients suggested that ADT plus EBRT to the prostate was associated with improved OS as compared to ADT alone in men with low-volume metastatic burden (HR, 0.68, 95% CI, 0.54–0.87); however, this result was not observed in those with high-volume disease (HR, 1.1, 95% CI, 0.92–1.2). 28 Prostatectomy may also improve the oncologic outcomes in patients with oligometastatic prostate cancer. 31 The definitive treatments, either radiation or prostatectomy, may be associated with survival benefit in patients with low metastatic burden.…”
Section: The Rationale For a Paradigm Shift From The “All-comers” Toward The “Personalized” Approachmentioning
confidence: 99%